(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Mediastinum is a wide space containing a lot of vital structures. Medaistinal masses represent a wide diversity of disease states. The location and composition of a mass is critical to narrowing the differential diagnosis. Distribution of mediastinum in to 3 compartments and presence of masses therein has been documented; however a tissue diagnosis is always essential to initiate the treatment. CT scan is successful in giving a diagnosis in many cases through a biopsy. Still many more require an aggressive measure like surgical intervention. Material & Methods: From January 2009 to December 2011, 110 cases of Medaistinal mass were referred to our department and in all cases CT guided biopsy was not possible or fruitless. Results: 77 cases had anterior-superior Medaistinal mass, 23 cases had posterior Medaistinal mass and 10 had middle Medaistinal mass. Respiratory symptoms were present in 73 of cases while 37 cases were asymptomatic. Major surgical procedures for obtaining tissue were Medianostomy42, VATS 34, Sternotomy 14, Anterolateral thoracotomy 8 and Posterolateral thoracotomy 12. Major diagnostic outcome were Granulomatous involvement 36, thymic masses and Primary/secondary carcinoma 21 each. No mortality was reported. 95 cases went eventless. Conclusion: We conclude that Surgery is safest and most accurate tool in diagnosis of Medaistinal mass.